Results of a prospective 6-year observational study of the efficacy and safety of a bioactive concentrate of small marine fish in senile patients with knee osteoarthritis and multimorbidity - M. V. Letaeva; M. V. Koroleva; T. A. Raskina; O. S. Malyshenko; Yu. V. Averkieva; E. V. Usova (Современная ревматология)
Objective: to evaluate the efficacy and safety of Alflutop therapy in elderly patients (75–90 years old) with knee osteoarthritis (OA) and multimorbidity based on the results of a prospective 6-year follow-up.Patients and methods. The study included 38 elderly women with knee OA (according to ACR criteria, 1986) stage II–III by Kellgren–Lawrence grading system, with pain ≥40 mm by visual analogue scale (VAS), who needed to take non-steroidal anti-inflammatory drugs (NSAIDs). Alflutop was administered as 1 ml intramuscular injections 20 consecutive days with a 6-month interval (12 courses). The effectiveness of therapy was assessed by VAS, WOMAC index and EQ-5D questionnaire. The safety of therapy was monitored throughout the observation period. The duration of the study was 6 years.Results and discussion. The full course of treatment with Alflutop was completed by 29 (76.3%) patients. Nine (23.7%) patients discontinued the study due to their inability to visit the treatment center (for reasons unrelated to the study).In elderly patients with knee OA, high level of multimorbidity was revealed, 5 comorbidities on average.There was a significant decrease in pain according to VAS (≥20%): by visit (V) 1 – in 76.3%, by V2 – in 71.0%, by V3 – in 68.4%, by V4 – in 63.1% and by V5 – in 55.2% of patients. By the 21st day of Alflutop therapy, a statistically significant decrease in the total WOMAC index (p<0.001) and an improvement in the quality of life according to the EQ-5D questionnaire (p=0.016) were found. These indicators remained relatively stable throughout the follow-up. By the 12th month, a decrease of the need of NSAIDs was registered (p=0.005).X-ray progression of OA stage ≥1 according to Kellgren–Lawrence on Alflutop therapy after 36 months of observation was recorded in 10.5% of patients, after 72 months – in 50.0%. No serious adverse events were registered during entire observation period.Conclusion. The results of a 6-year prospective study demonstrate the high efficacy of Alflutop in elderly patients with knee OA. The obtained data confirm the safety of long-term treatment with this drug in elderly patients with high multimorbidity, which makes it the first-line drug in the complex therapy of OA.